ANALISIS PENERAPAN SISTEM AKUNTANSI MANAJEMEN TERHADAP PEGENDALIAN KUALITAS PRODUK DI PT.EMPAT SAUDARA MANADO - Butarbutar, Janrilius Doli; Karamoy, Herman; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2017)
The development of management accounting system is now very rapid. Company managers require management information systems to implement planning, control and decision-making functions. Management accounting systems are systems that collect operational and financial data, process, store and report to users, ie workers, managers, and executives. The purpose of this research is to know the application of management accounting system to product quality control at PT.Empat Saudara Manado. The method used is descriptive qualitative. The results of the application of management accounting system in PT.Ampat Saudara manado has shown its role as a tool in controlling product quality, and can help managers to be better prepared in facing company problems and control product quality. PT.Empat Saudara manado only need to maintain it so that in megontrol every part there is no errorsin every running process.Keywords: management accounting system, Product Quality Control, SAM Characteristics.